Provoz a řízení klubu sportovní brokové střelby - Herberger, Daniel (Vysoké učení technické v Brně. Fakulta podnikatelská)
Předmětem této práce je analýza, zhodnocení a následné návrhy na zlepšení provozu sportovně střeleckého klubu SSK Activ Sport. V teoretické části jsou popsána teoretická východiska související s danou problematikou, praktická část je zaměřena na analýzu současného stavu klubu, jeho konkurence a z toho vyplívající návrhy na zlepšení jak provozu, tak marketingu klubu.

The object of this work is the analysis, evaluation, and subsequent proposals to improve the operation of sport shooting club SSK Activ Sport. The theoretical part describes the theoretical background related to the issue, the practical part is focused on the analysis of the current state of the club, its competitors and the revenues resulting suggestions for improvement in both service and marketing club.
Operation and Managment of Shootgun Shooting Sports Club
Keywords: Management; marketing; sponzorování; sport; sportovně střelecký klub; SSK Activ Sport; Český střelecký svaz; Management; marketing; sponzoring; sport; shooting sport club; SSK Activ Sport